Jay Marketing's strategic plan towards becoming a competitive company - Li, Josephine K. (School of Management, University of the Philippines Mindanao, 2007)
Jay Marketing is a local retail business established in 1993 under sole ownership. In 1998, the company ventured into an outlet merchandising agreement with Company X which started their expansion from one store to seventeen outlets, and from a handful to 70 employees. As the company grows, it faces a major challenge to attain competitive advantage. In view of this, the management started taking steps towards improvement. These steps included the creation of an organizational structure and the writing down of some major processes and credit policies. The company was studied using the Pearce and Robinson framework. Data utilized were gathered from company records and from interviews with the proprietor and a few key personnel. The company's internal strengths and weaknesses were identified through SWOT analysis. The strengths were openness to initiate change, alliance with Company X, ability to maintain good financial standing, and not having long-term debts. Weaknesses mostly revolve around inefficient processes or systems. The 2.34 IFE score is below the 2.5 benchmark. This shows that the company is in an internally weak position. The external factors are remote (socio-economic, politico-legal and technological) and industry environments. The SWOT tool was used to analyze the remote environment. The industry environment was analyzed using Michael Porter's five forces model. Good economic and political forecasts are counted as opportunities while the opposite are seen as threats. The score of 2.03 in the EFE matrix shows that the company is not in a good position to exploit opportunities and counter threats coming from the environment. The five forces model result showed a low-medium threat of entry, high supplier power, low-medium buyer power, very low threat of substitute, and medium threat from competitors. The strategy selection matrix came up with four options: reorganization, out-sourcing, concentrated growth and market development, and strategic alliance. Reorganization was chosen as the most suitable option. This is because the reorganization strategy will help the company focus on overcoming its internal weaknesses first. Resolving the company's weaknesses will in the process strengthen its foundation. A solid foundation will increase the strengths of the company. With more strengths to build on, the company can then venture into maximizing its strengths. During implementation, control are established to monitor, control and evaluate the success or failure of a strategy. Controls for key function areas are: percentage goal increases (sales, equity, IFE/ EFE scores) and decreases(operational costs, employee turnover, accounts payable), observation of new processes (structure, data sharing, inventory monitoring, reporting), and the development of new programs (HR, marketing). This process will provide results that will guide the company towards continuous improvement.